Pemanfaatan Limbah Lumpur Industri Crumb Rubber Sebagai Adsorben Ion Cr(VI) yang Diaktivasi dengan H3PO4 - Resti Hariyani; Salmariza Sy; Mawardi Mawardi (Jurnal Periodic Jurusan Kimia UNP, 2013)
Utilization of sludge waste from wastewater treatment system using active sludge systems of Crumb Rubber Industry PT.Teluk Luas Lubuk Begalung Padang to be activated carbon that was activated by H3PO4 as adsorbent of ions Cr (VI) has been done. Characterization of activated carbon was conducted according to SNI 06-3730-1995, including the determination of iodine absorption, moisture content, and the amount of carbon bound. Besides, this research was also conducted using batch system treatment to activated carbon and inactivated carbon, including pH, contact time, and initial concentration of solution. The equation of Langmuir Isotherm was used to determine maximum capacity of activated carbon adsorption to Cr (VI). Results showed that the absorption of iodine was 48,26%, moisture content was 0.14%, and carbon bound was 24,925%. The optimum pH,  the contact time   and optimum concentration  respectively was pH3, 60 minutes and 50 mg/L for an activated carbon adsorbent and  pH2,  120 minutes and 50 mg/L for inactivated carbon adsorbent. The activator influenced to the adsorption of Cr(VI). The determination of the optimum adsorption for activated carbon adsorbent was 1,11 and 1,99 mg/g, meanwhile for inactivated carbon, it was 0,08 and 1,16 mg/g.